Effects of Using Multiple Hands and Fingers on Haptic Performance. (July 2013) - Morash, Valerie S; Pensky, Allison E Connell; Miele, Joshua A
It remains controversial whether using two hands and multiple fingers provides any perceptual advantage over a single index finger. The present study examines this long-running question in the haptic-exploration literature by applying rigorous, psychophysical, and mathematical modeling techniques. We compared the performance of fourteen blindfolded sighted participants on seven tactile-map tasks using seven finger conditions. All tasks were benefited by multiple fingers, but it varied whether multiple fingers were beneficial on one hand, two hands, or both. Line-tracing tasks were performed faster when two hands were used, but not more than one finger per hand. Local and global search tasks were faster with multiple fingers, but not two hands. Distance comparison tasks were also performed faster with multiple fingers, and sometimes with two hands. Lastly, moving in a straight line was faster with multiple fingers, but was especially difficult with just two index fingers. These results provide empirical evidence that multiple hands and fingers benefit haptic perception, but the benefits are more complex than simply extending the tactile field of 'view'. This analogy between touch and vision fails to account for the autonomous movements and sensations of the fingers, which we show benefit the haptic perceptual system.